The social environment and childhood obesity: Implications for research and practice in the United States and countries in Latin America. (5th May 2021) - Ayala, Guadalupe X.; Monge‐Rojas, Rafael; King, Abby C.; Hunter, Ruth; Berge, Jerica M.
Summary: The environments of children influence their risk for childhood obesity through, among other factors, a child's weight‐related behaviors (i.e., diet and physical activity). In this article, we present evidence on social environmental factors associated with a child's diet and physical activity, and more generally, the prevention and control of childhood obesity among Hispanic/Latinx children in the United States and children from countries in Latin America. Using a socio‐ecologic lens, we present evidence from cross‐sectional and longitudinal studies conducted in the United States involving Hispanic/Latinx children, and evidence from studies involving children in Latin America. Studies examining parenting factors in the home environment (e.g., parenting strategies) are especially emphasized, with more limited evidence on social environmental factors in other lived contexts (e.g., school). The influence of acculturation on social relationships cuts across levels of the socio‐ecological framework. Intervention research identified strategies and research gaps for intervening on social factors to promote healthy behaviors and reduce risk for childhood obesity. Community health workers and others forms of peer support were identified as relevant approaches at multiple levels of the socio‐ecological framework. This article concludes with directions for future research to further understand the environment using newer information and communication technologies.